A new species of Scrophularia (Scrophulariaceae) from Hubei, China - Wang, Rui-Hong; Xia, Mao-Qin; Tan, Jin-Bo; Chen, Chuan; Jin, Xin-Jie; Li, Pan; Fu, Cheng-Xin (Phytotaxa, 2018)
A new species, Scrophularia jinii (Scrophulariaceae), from Central China is described and illustrated. This new species was formerly misidentified as S. fargesii, from which it differs in many morphological characters. Moreover, it is distinct with all known Scrophularia species in its unique deeply double serrate leaf margin with 3–7 big teeth on each side. Molecular phylogenetic analysis further supports its species delimitation and suggests a close relationship with several Japanese and North American species.